Solid-state fermentation using wheat bran to produce glucose syrup and functional cereal bars - Figueiredo, Célia Cristina Malaguti [UNESP]; Granero, Filipe Oliveira [UNESP]; Silva, Luciana Pereira; Nogueira, Ilca Fabiane Amâncio [UNESP]; de Souza, Joyce Faria [UNESP]; Escaramboni, Bruna [UNESP]; de Oliva Neto, Pedro [UNESP]; da Silva, Regildo Márcio Gonçalves [UNESP] (Springer Nature, 2024)
Wheat bran is one of the most abundant by-products from grain milling, which can be used as substrate for solid-state fermentation (SSF) to obtain enzymes able to convert this agro-industrial waste into glucose syrup, which in turn can be applied for the production of different food products. The present study aimed to determine centesimal composition of wheat bran, obtain enzymatic extract that converts wheat bran into wheat glucose syrup (WGS), produce rice flakes cereal bars (RFCB), and evaluate their nutritional composition and the presence of functional compounds, as well as their antioxidant potential. Determination of centesimal composition of wheat bran demonstrated its nutritional potential. Enzymatic extract was obtained and it converted wheat bran into WGS, which were applied to rice flakes producing RFCB. These cereal bars proved to be a source of dietary fiber (1.8 g) and soluble protein (7.2 g) while RCFB produced with corn glucose syrup did not present these nutritional components. In addition, RFCB produced with WGS showed polyphenolic compounds, among them flavonoids, which exhibited antioxidant activity by DPPH and ABTS radical scavenging (47.46% and 711.89 μM Trolox Equivalent/g, respectively), and iron ion reduction (71.70 μM Trolox equivalent/g). Final product showed a decrease in caloric value and sodium content. Therefore, the present study showed that the bioprocess of SSF yields a nutritional, ecological, and functional food product, which might be of great interest for food industry, adding nutritional and functional value to a well-stablished product.
Keywords: Agro-industrial waste; Bioactive compounds; Cereal bars; Convenience food; Rice flakes